Non-Aqueous Dispersion (NAD) Polymerisation-Based Synthetic Route to Hypercrosslinked Polymer with High Specific Surface Areas - Norhayati, Abdullah; Cormack, Peter A. G. (Trans Tech Publications, Switzerland, 2016)
Hypercrosslinked polymer microspheres with high specific surface areas were prepared successfully by exposing reactive, gel-type polymer precursors to a Friedel-Crafts catalyst. The lightly crosslinked gel-type polymer precursors were synthesised by non-aqueous dispersion (NAD) polymerisation in microsphere form, and were used subsequently in hypercrosslinking reactions. Extensive microporosity was generated in the products, leading to remarkably high inner specific surface areas of up to ~1,500 m2/g. SEM and BET spectroscopy were used to monitor the course of the hypercrosslinking reactions.